Republic of Latvia : Staff Report for the 2000 Article IV Consultation and First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2000)
With the resumption in growth, the economic recession triggered by the Russian crisis has ended. Additional efforts will be needed to reduce the current account deficit and increase its financing. The IMF staff commend the intention to streamline tax benefits granted to enterprises and to eliminate the benefits that are inconsistent with EU regulations. Financial sector development is imperative for continued external sustainability and economic growth. The government's ability to implement the privatization program and address the remaining impediments to an enabling business climate is crucial.